Maori identities; fixed, forced, and fluid - McIntosh, Tracey (New Zealand identities: departures and destinations, 2005)
Social scientists attached to the Centre for Applied Cross Cultural Research at Victoria University of Wellington examine issues of New Zealand identity.
Keywords: ethnic identity; ethnicity; identity

Indigenous Insider Knowledge and Prison Identity - McIntosh, Tracey; Coster, Stan (Counterfutures, 2017)
This article draws on the personal experiences and state documentation of Stan Coster (Ngāti Kahungungu) whose life has been characterised by different forms of state confinement, including over 25 years in prison serving both short and long lags. Through the use of the Official Information Act, Stan recovered state documentation on himself spanning over 40 years. Stan is not a research participant, but a full research collaborator and is engaged in all elements of this paper, so while not a writer he is both auteur and author of this piece. Stan’s story is his own and yet many of its features speak to a much broader collective experience. His prison identity and gang identity can be seen as being both informed and generated by state sponsored activity. By traversing the issues that pertain to the crisis of mass imprisonment, Māori disproportionality in the prison system, the contribution of the state to prison, and gang identity, we look at the possibilities of drawing on knowledge acquired under conditions of state constraint.
Keywords: crown policy; crown violence; identity; incarceration; marginalisation; prison

Mana whenua, mana moana, mana tinana, mana momona - Gillon, Ashlea; Le Grice, Jade; Webber, Melinda; McIntosh, Tracey (New Zealand Sociology, 2022)
The ways in which we understand bodies and fatness are complex. While coloniality unduly influences and shapes normative meanings of the body in everyday contexts, Maori conceptualisations of the b...
Keywords: identity; self-identification; te ao Māori